The Influence of Product and Facade Design towards Consumer Preferences - Imanuel mbake; Marianus Bahantwelu (Talenta Publisher, 2021)
The façade is an architectural element that is to show the functional and meaning of the building. The façade design of a house is generally on the of the basic considerations for consumers to buy. In addition, the face design has always been a promotional information in the marketing mis that used by housing developers. This study was intended to identity the effect of product and façade design towards consumer preferences in lower-middle housing. The object study was Pondok Indah Matani housing in Kupang, NTT. This study used experimental approach by manipulating research variables. The manipulated variables were product and façade design, while the influenced variables were consumer preferences. The determination of sample used purposive sampling method with a technical survey using a questionnaire. The result of study stated that the product and façade design had a significant effect on consumer preferences, through (1) the application of contrasting colors, (2) the firm boundaries in transition area in front of the house and (3) the complexity of the product dan façade design should be not too complicated so that it was easy to care post purchase.